Sistem Ekonomi Politik Kapital sebagai Isu Hubungan Internasional: Perbandingan Dampak Sistem Kapital terhadap Kesejahteraan Sosial Menurut Perspektif Konvensional dan Islam - Putri, Mia Utami; Nur Azizah, Meiliani; Regita Cahyani Muis, Afni (UIN ALAUDDIN MAKASSAR, 2023)
The Capitalist Economic System prioritizes individual freedom by maintaining market mechanisms to improve their economy, and trying to obtain maximum profits. On the other hand, there is an Islamic political economy which has a sharia basis by strengthening the role of 'Ukhuwah Islamiyah' so that social inequality does not occur between communities. This research will discuss the differences in the impact of the capitalist economic system from the perspective of Islamic and conventional political economy on the welfare of society. This research uses a qualitative-descriptive method by making literature reviews as the unit to search the main datas. The research findings in this research are that there are significant differences between the capitalist system based on an Islamic perspective and conventional ones based on fundamental values, principles and ultimate goals.